The Nonstandard Language Variation in Instagram Headlines of @folkative - Anastasya B W Nadeak; Cindy C Nadeak; Helda H Hia; Jesika P Sitorus; Meisuri Meisuri; Nurjasni Nurjasni; Ruth Manurung (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study investigates the occurrence and functions of nonstandard language variation in Instagram headlines posted by @folkative, a popular digital media account known for its creative use of informal language. Despite the growing attention to social media discourse, little research has focused on how nonstandard forms operate in short, attention-grabbing digital headlines. Guided by Labov’s (1972) variationist sociolinguistic framework, this study employs a descriptive qualitative method complemented by simple quantification. The data consist of headlines uploaded by @folkative throughout September 2025. The analysis reveals four main types of nonstandard variation: code-mixing, nonstandard spelling, colloquial expressions, and lexical innovation. Among these, code-mixing appears most frequently (33.93%). The use of nonstandard language is not arbitrary but rather reflects deliberate stylistic and social choices. These variations serve several communicative and pragmatic functions, including attracting readers’ attention, conveying humor, saving space within limited character counts, expressing solidarity with followers, and constructing a modern, cosmopolitan online identity. The findings demonstrate that nonstandard language in Instagram headlines contributes to meaning-making and audience engagement, showing how Indonesian users creatively manipulate linguistic resources to suit digital communication norms.